2011
DOI: 10.1177/0003319711398864
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Chronic Kidney Disease and SYNTAX Score

Abstract: Chronic kidney disease (CKD) is associated with increased risk of cardiovascular disease and death. We evaluated the association between CKD and severity of coronary artery stenosis by calculating SYNTAX Score in patients with left main coronary artery and/or 3-vessel coronary artery disease. Coronary angiograms of 217 patients were assessed. Chronic kidney disease was staged using the estimated glomerular filtration rate (eGFR, mL/min per 1.73 m(2)) prior to coronary angiography. Patients were divided into 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 33 publications
4
27
4
Order By: Relevance
“…Lesion complexity increases progressively with decreasing kidney function with GFR a strong predictor of higher SYNTAX (SYNergy between PCI with TAXUS™ and Cardiac Surgery) Score [47]. However, patients with impaired renal function are much less likely than patients with normal renal function to undergo PCI.…”
Section: Percutaneous Coronary Intervention (Pci)mentioning
confidence: 99%
“…Lesion complexity increases progressively with decreasing kidney function with GFR a strong predictor of higher SYNTAX (SYNergy between PCI with TAXUS™ and Cardiac Surgery) Score [47]. However, patients with impaired renal function are much less likely than patients with normal renal function to undergo PCI.…”
Section: Percutaneous Coronary Intervention (Pci)mentioning
confidence: 99%
“…may increase mortality because of the patients' complex coronary anatomy on admission and the high number of lesions. Coskun et al [17] showed in their study that low GFR values before angiography are an independent predictor of a high Sx score.…”
Section: Discussionmentioning
confidence: 94%
“…Goodman et al [19] reported that CAD is common in young adult patients with endstage renal disease. Kılıckesmez et al [6,7] examined 216 coronary angiographies of patients with normal renal function and different stages of renal dysfunction and identified coronary lesion complexity according to the ACC/AHA lesion classification. [20] The frequency of complex lesions was higher in the renal failure group.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] A strong relationship between severe renal dysfunction, and extent and complexity of coronary artery disease (CAD) has been investigated in only a few previous studies. [5][6][7] It has been demonstrated that even a slight decrease in the GFR poses an independent risk factor for cardiovascular diseases. [8] However, this association was not investigated in patients with stable CAD and normal to mildly impaired renal function.…”
mentioning
confidence: 99%